Enhancing Physical Adaptation and Functional Independence in Post-Stroke Patients Through Motivational Interviewing-Based Health Coaching - Bernadetta Germia Aridamayanti; Shenda Maulina Wulandari; Maulidya Septiany; Agianto; Chrisnawati (Masters Program in Public Health, 2026)
Background: Stroke is a leading cause of long-term disability worldwide and is highly prevalent in Indonesia, especially in underserved and geographically isolated regions such as riverside communities. Many stroke survivors struggle with impaired physical adaptation and low functional independence. This study aimed to evaluate the effectiveness of motivational interviewing-based health coaching, guided by the Roy Adaptation Model, on improving physical adaptation and functional independence among post-stroke patients in Banjar Regency. Subjects and Method: A quasi-experimental study with a pre-test and post-test control group design was conducted from January to April 2025 in two riverside subdistricts of Banjar Regency, South Kalimantan. A total of 90 post-stroke patients aged ≥45 years were recruited through purposive sampling. Participants were assigned to either the intervention (n=45) or control group (n=45). The intervention group received six sessions of structured health coaching based on motivational interviewing principles, while the control group received routine care. Physical adaptation was measured using the Roy Adaptation Assessment Guide (RAAG), and functional independence was assessed using the Barthel Index. Data were analyzed using the paired t-test and Mann–Whitney U test. Results: The intervention group showed significant improvements in physical adaptation (Mean pre-test=54.87; post-test=66.02; p<0.001) and functional independence (Mean pre-test=60.44; post-test=78.91; p<0.001). In contrast, the control group showed no significant changes in physical adaptation (p=0.062) or functional independence (p=0.084). Between-group comparisons at post-test showed significantly higher scores in the intervention group for both physical adaptation (p<0.001) and functional independence (p<0.001). Conclusion: Motivational interviewing-based health coaching significantly improves physical adaptation and functional independence among post-stroke patients in riverside communities. Integrating this approach into community-based rehabilitation may enhance recovery outcomes in underserved areas.